Pelatihan Pendirian dan Tata Kelola Bank Desa Untuk Pengembangan Ekonomi dan Kesejahteraan Masyarakat Desa Sumberdem - M. Yusuf Azwar Anas; Yuliyanti M. Manan (Fakultas Sains Dan Teknologi, Universitas Raden Rahmat Malang, 2024)
Rural development and microfinance sustainability are the main focus to address the gap between urban and rural areas. Based on the National Medium-Term Development Plan (RPJMN) 2020-2024, Indonesia prioritizes rural development with the allocation of village funds from the state budget since 2015. The training on the establishment and governance of Village Banks is the first step in establishing village banks and increasing financial inclusion in rural areas. The training implementation method includes problem identification, preparation of training materials, training implementation, and sustainability evaluation. The training activities held in Sumberdem Village involved various parties, such as community leaders, village officials, BUMDES administrators, and KKN UNIRA Malang students. The training materials included business planning, the process of establishing a village bank, good governance, and the products and services that can be offered by the Village Bank. Interactive discussions and simulations were used to provide participants with a comprehensive understanding. A follow-up mentoring program will be conducted to help implement the knowledge gained in real practice.